Cinnamoyl–Coumarin Hybrid Derivatives with Remarkable Fluorescent Molecular-Rotor Properties in Mixtures of Dppc:Dopc Luvs - Aspee-Lamas, A; Zúñiga-Núñez, D; Mura-Mardones, F (Elsevier Ltd, 2020)
Cinnamoyl coumarin probes acting as fluorescent molecular-rotors were used for evaluating microenvironments in DPPC:DOPC liposomes. For this purpose, derivatization with aliphatic chains between 5 and 12 carbons was used for maximizing interaction with lipid membranes. These probes showed a decrease in the fluorescence intensities and hypsochromic shifts in fluid DOPC and DPPC:DOPC in comparison with DPPC. In particular, for C–CH-5 and C–CH-12, in DPPC:DOPC (1:1) were observed shorter fluorescence lifetimes τ1 associated to the TICT excited state, as well as, an increase on the contribution of the τ3 associated to the ICT excited state, in comparison with other lipid proportions and even pure DPPC and DOPC. Interestingly, all the probes showed one rotational correlation time φ1 in DPPC associated with the restricted environment. However, in fluid DOPC and DPPC:DOPC lipid membranes, the long aliphatic chain probes (C–CH-8, 10, and 12) exhibited a faster rotational correlation time φ1 than in DPPC and also a larger φ2, that indicate the existence of two different environments. The most favorable orientations for C–CH-8 cinnamoyl–coumarin was estimated by employing Molecular Dynamics simulation and an enhanced sampling method. Moreover, the results show two energetic minima corresponding to the most favorable orientations of the probe in the mixture of DPPC:DOPC. These orientations are surrounded by different lipid compositions, which would explain the two rotational correlation times in the lipid mixture. © 2020 Elsevier Ltd